DETERMINATION OF SOME MARINE METEOROLOGICAL EXTREME VALUES AND ITS RELATION WITH DISTRIBUTION OF SURFACE WATER RESOURCES ON THE LY SON ISLAND - Thong, Bui Xuan; Dat, Le Tuan; Chau, Truong Viet (Vietnam Journal of Marine Science and Technology, 2018)
Climate change in terms of marine meteorological extreme values has direct impact on distribution of surface water resources on the island. Based on a series of marine meteorological data collected in the period 1985 - 2012 at the Ly Son station we have determined some extreme values such as maximum precipitation, evaporation, air temperature, sea level and other oceanographic elements. The present study tries to reveal some relationships between marine meteorological extreme values and distribution of surface water resources under condition of Ly Son island. The precipitation of < 50 mm, 50 - 100 mm and > 100 mm has the frequency of 57.8%, 20.7%, and 21.5% respectively. Due to climate change, the air temperature has the increasing tendency for all three states of medium, maximum and minimum values. Sea level and other oceanographic phenomena also have the increasing tendency. The calculation results show that the average annual surface runoff is 13.9 million m3/year and the water volume per capita reaches 678 m3/person/year. According to criteria of International Water Resources Association, a country with a water volume per capita off less than 4,000 m3/person/year is considered as country of water shortage.